Kinematics Analysis of a 6-DOF Collapsible Manipulator - Li Hui; Zheng Xiangzhou; Yuan Yanfang; Yu Jingjing (Jixie chuandong)
Because of the widely applications of robots,the labor productivity is greatly enhanced and the working environment is improved. The kinematics analysis of manipulator is a basis for achieving accurate motion control. The kinematics of a kind of 6- DOF collapsible manipulator is studied,the forward and inverse kinematics within the scope of joint angles is obtained according to the geometric characteristics of robot,by using the MATLAB,the verification of kinematics simulation is carried out.